2022
DOI: 10.1039/d2ra00124a
|View full text |Cite
|
Sign up to set email alerts
|

Nano-silver functionalized spherical activated carbon with enhanced dipropyl sulfide adsorption capacity and antibacterial properties

Abstract: A kind of functional composite was prepared by loading silver nanoparticles firmly on the surface of spherical activated carbon, which showed chemical adsorption properties for chemical warfare agents and satisfactory antibacterial activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…However, due to the high toxicity and strict control of sulfur mustard, some chemicals such as dipropyl sulfide (DPS), with a similar chemical structure and lower toxicity, have also been used as a simulator of a chemical warfare agent for research in the lab [ 13 , 14 ]. For example, YANG et al [ 15 ] used nano-metal modified spherical activated carbon and used it as an adsorbent for the adsorption of DPS; the result showed that the equilibrium adsorption capacity of modified SAC towards DPS increased by 13.41% compared with that of pristine SAC, and the maximum adsorption capacity could be up to 34.34 mg/g. However, the spherical activated carbon used in protective clothing still suffers from some problems, such as its relatively low adsorption speed, its ease of falling off the cloth, and the insufficient utilization of pore structures due to the coverage of adhesive.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the high toxicity and strict control of sulfur mustard, some chemicals such as dipropyl sulfide (DPS), with a similar chemical structure and lower toxicity, have also been used as a simulator of a chemical warfare agent for research in the lab [ 13 , 14 ]. For example, YANG et al [ 15 ] used nano-metal modified spherical activated carbon and used it as an adsorbent for the adsorption of DPS; the result showed that the equilibrium adsorption capacity of modified SAC towards DPS increased by 13.41% compared with that of pristine SAC, and the maximum adsorption capacity could be up to 34.34 mg/g. However, the spherical activated carbon used in protective clothing still suffers from some problems, such as its relatively low adsorption speed, its ease of falling off the cloth, and the insufficient utilization of pore structures due to the coverage of adhesive.…”
Section: Introductionmentioning
confidence: 99%
“…10 As a new antibacterial material, nano Ag has excellent antibacterial stability, high activity, low toxicity and broad-spectrum antibacterial advantages. 11,12 The development of nano Ag and nano Ag-based composite materials has rapidly attracted extensive attention of researchers. Changing the physical and chemical properties of nano Ag can improve its germicidal efficacy, such as the particle size, dispersion, surface charge and other properties of nano Ag.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially true of metallic nanoparticles and the metal oxides that correspond to them, such as copper [16], silver [17], titanium oxide [18], and zinc oxide [19]. By impregnating activated carbon with silver or metallic oxides, it is possible to create a material having antibacterial properties [20,21]. Producing Ag NPs supported on an activated carbon matrix may be done in a number of methods.…”
Section: Introductionmentioning
confidence: 99%